The Prevalence of Iron Deficiency Anemia (IDA) in Adolescent Girls: A Literature Review - Adila, Indi; Prajnaparamita, Irfani (Journal of Diverse Medical Research: Medicosphere, 2025)
Abstract Background. Anemia is a condition when the number of red blood cells decreases to meet the physiological needs of the body. It is estimated that about 30% of the world's population suffers from anemia, and more than half of them are iron deficiency anemia. This review of various literatures intends to determine the prevalence of iron deficiency anemia in adolescent girls, which by knowing this we can determine more targeted prevention and treatment strategies. Methods. The method used in this literature review is a literature search using keywords that match the topic through several databases such as PubMed, ScienceDirect and Google Scholar. The literature used is literature with a maximum publication year of 2019 or the last 5 years. The results obtained the prevalence of iron deficiency anemia in adolescent girls. Discussion. All journals discussed the prevalence of iron deficiency anemia in adolescent girls with the majority using cross-sectional and NHANES methods. Key findings include that the prevalence of anemia varies based on factors such as age, nutrition, menstrual cycle, and level of knowledge. General strengths include valid and relevant data, while weaknesses include limited generalizability, lack of analysis of specific factors, and terms that are complicated for lay readers. Conclusion. The prevalence rate of iron deficiency anemia in adolescent girls is still relatively low.